Impacts of 2-bromoethanesulfonic sodium on methanogenesis: Methanogen metabolism and community structure. (15th February 2023) - Qiu, Shuang; Xia, Wenhao; Xu, Jiajie; Li, Zimu; Ge, Shijian
Highlights: Molecular mechanism underlying BES inhibition on CH4 production was revealed. Inhibition was induced by competition between analog BES and methyl-CoM/CoM. BES suppressed acetoclastic methanogenesis but enriched hydrogenotrophic one. BES inhibited electron transport and ATP synthesis but enhanced ATP consumption. BES decreased EPS secretion and destructed sludge surface. Abstract: Production of medium-chain carboxylic acids (MCCAs) by chain elongation (CE) presents a competitive alternative to conventional products of methane in anaerobic digestion treating organic waste streams, considering energy recovery, economic, and environmental profits. However, the system stability and performance largely rely on the selective suppression of methanogens while stimulation of CE bacteria. Commercial inhibitors such as 2-bromoethanesulfonic sodium (BES) was shown to be effective, but controversial conclusions exist on its inhibition characteristics and the inhibition mechanism remains unclear. Therefore, this study systematically investigated the responses of methanogenesis in granular sludge to various BES levels, focusing on methane production, methanogenic pathway, dynamic populations, electron transport and energy metabolism. Results showed that compared with the control, 3.0 g/L BES was sufficient to induce a 72.9% reduced level on accumulative methane production by the end of 4 cycles (28 days), which was likely to be attributed to the significantly suppressed metabolic pathways and intracellular regulations. Specifically, BES suppressed the electron transport via unproper electron carriers and reduced electron amount as indicated by the decreased level of enzymes and genes involved such as coenzyme F420, CO dehydrogenase and NADH:ubiquinone reductase (H + -translocating). Moreover, BES regulated the intracellular energy metabolism, leading to the impeded ATP synthesis but enhanced ATP consumption as evidenced by the variations on the activity or abundance of acetate kinase, A1Ao-ATP synthase, nitrogenase and ATP citrate synthase. Additionally, BES enriched hydrogenotrophic methanogenesis over acetoclastic one as supported by variations on the archaeal community structures and regulations of differentially expressed genes involved. Moreover, BES also reduced the contents of both protein and carbohydrate in extracellular polymeric substances (EPS). This study is expected to enhance understanding of BES contribution to methanogenesis inhibition but MCCAs production in CE bioreactors. Graphical abstract: Image, graphical abstract